Multilocus sequence typing (MLST) of Mycoplasma hyopneumoniae: A diverse pathogen with limited clonality - Mayor, D.; Jores, Joerg; Korczak, B.M.; Kuhnert, P. (Elsevier, 2008)
A multilocus sequence typing (MLST) scheme was established and evaluated for Mycoplasma hyopneumoniae, the etiologic agent of enzootic pneumonia in swine with the aim of defining strains. Putative target genes were selected by genome sequence comparisons. Out of 12 housekeeping genes chosen and experimentally validated, the 7 genes efp, metG, pgiB, recA, adk, rpoB, and tpiA were finally used to establish the MLST scheme. Their usefulness was assessed individually and in combination using a set of well-defined field samples and strains of M. hyopneumoniae. A reduction to the three targets showing highest variation (adk, rpoB, and tpiA) was possible resulting in the same number of sequence types as using the seven targets. The established MLST approach was compared with the recently described typing method using the serine-rich repeat motif-encoding region of the p146 gene. There was coherence between the two methods, but MLST resulted in a slightly higher resolution. Farms recognized to be affected by enzootic pneumonia were always associated with a single M. hyopneumoniae clone, which in most cases differed from farm to farm. However, farms in close geographic or operational contact showed identical clones as defined by MLST typing. Population analysis showed that recombination in M. hyopneumoniae occurs and that strains are very diverse with only limited clonality observed. Elaborate classical MLST schemes using multiple targets for M. hyopneumoniae might therefore be of limited value. In contrast, MLST typing of M. hyopneumoniae using the three genes adk, rpoB, and tpiA seems to be sufficient for epidemiological investigations by direct amplification of target genes from lysate of clinical material without prior cultivation.